Peningkatan Kompetensi Keuangan Syariah Santri melalui Program Pelatihan Manajemen Keuangan dan Simpan Pinjam - Heni Kurnia Wati; M. Arif Musthofa; Al-Munip (SiNORA, 2025)
Financial management based on Sharia principles is a crucial aspect in shaping the competence, ethics, and character of santri in facing modern economic challenges. This study aims to evaluate the effectiveness of the Sharia-based financial management and savings-loan training program at Pondok Pesantren Warisan Rasulullah 4 in enhancing santri’s financial literacy and skills. The research employed a quantitative descriptive method with a pre- and post-training approach involving 50 santri over three days. Data were collected through financial literacy questionnaires, practical observation, and documentation of training activities. The results indicate a significant improvement in competencies, with 88% of santri correctly answering the financial literacy questionnaire, 82% successfully preparing simple financial reports, and 85% able to manage savings and loan transactions according to profit-sharing principles. These findings confirm that a combination of theoretical and practical methods is effective in developing ethical and Sharia-compliant financial skills, while also supporting the development of economic independence within the pesantren and empowering santri as agents of change in the community.